2015
DOI: 10.1007/s10936-015-9366-2
|View full text |Cite
|
Sign up to set email alerts
|

Styles and Style-Stretching: How are They Related to Successful Learning?

Abstract: Although the learning style construct has aroused much interest over the years, questions remain regarding basic issues such as definition, the validity and/or reliability of various measurement instruments, and the relationship between learning style and successful learning. Furthermore, although maintaining stylistic flexibility is recommended by many authors, few studies have attempted to relate the style-stretching concept to successful learning. This study therefore attempted to address these questions. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Learning style is a term that refers to the learner’s method (s) of gathering, processing, interpreting, organizing, and thinking about information 1,2. In literature, learning style is defined as “a set of factors, behaviors, and attitudes that facilitate learning for an individual in a given situation” and also defined as “people’s consistent ways of responding to and using stimuli in the context of learning” 2–4. In terms of instructional strategies, it defines as “the way through which students typically pursue the act of learning” 5.…”
Section: Introductionmentioning
confidence: 99%
“…Learning style is a term that refers to the learner’s method (s) of gathering, processing, interpreting, organizing, and thinking about information 1,2. In literature, learning style is defined as “a set of factors, behaviors, and attitudes that facilitate learning for an individual in a given situation” and also defined as “people’s consistent ways of responding to and using stimuli in the context of learning” 2–4. In terms of instructional strategies, it defines as “the way through which students typically pursue the act of learning” 5.…”
Section: Introductionmentioning
confidence: 99%
“…Third, while this study describes a discussion of stabilitystretchability, it does not refer to any empirical data regarding this matter. In previous findings, while many researchers have expressed their opinions on this issue, there has been very little empirical study (e.g., Griffiths & İnceçay, 2016). However, as mentioned in the literature review, this issue would be very important for the purpose of applying the concept of cognitive styles to practical situations.…”
Section: Discussionmentioning
confidence: 99%
“…The previous findings have shown that cognitive styles seem to be partly stable (Richardson, 2011), affected by both genetic factors (Coffield et al, 2004) and early educational experiences (Kolb et al, 2001). On the other hand, many researchers have described the stretchability of cognitive styles (Cohen, 2010;Dörnyei, 2005;Oxford, 2011), which is also supported by several empirical studies (Griffiths & İnceçay, 2016). However, based on some traditional theories, cognitive styles are more stable than other aspects of learning styles (Curry, 1983).…”
Section: Japanese Adult Efl Learnersmentioning
confidence: 92%
“…In a different approach, Griffiths and İnceçay (2016) introduced learning style stretching, a concept that sounds close to simple strategic teaching. Even though their study did not adequately address evidence in the ways that Pashler et al (2009) andCuevas (2015) claimed were necessary for proving a learning styles' existence, Griffiths and İnceçay's (2016) work was of value simply because it supported the idea that learners can increase their learning and achievement when they step out of their style comfort zone and try to employ different styles with which to learn material. This idea was congruent with Gardner's (2013) and Willingham et al's (2015) belief that learning different material requires the use of different learning methods and strategies that can be nourished and grown.…”
Section: Learning Styles In the Recent History Of Educationmentioning
confidence: 99%
“…This idea was congruent with Gardner's (2013) and Willingham et al's (2015) belief that learning different material requires the use of different learning methods and strategies that can be nourished and grown. Though Griffiths and İnceçay (2016) termed this style stretching, with only slight semantic alteration this could apply to abilities and traits. Also, Griffiths and İnceçay saw an increase in learning as per learners' willingness to style stretch as well as noted that more successful learners employed this method more often, thus giving educators more incentive to support the growth of style (or abilities) stretching in learners.…”
Section: Learning Styles In the Recent History Of Educationmentioning
confidence: 99%